2022
DOI: 10.1001/jamaoto.2022.2551
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of BMI and Venous Thromboembolism Rates in Patients on Standard Chemoprophylaxis Regimens After Undergoing Free Tissue Transfer to the Head and Neck

Abstract: ImportanceVenous thromboembolism (VTE) is a severe complication after free tissue transfer to the head and neck (H&N). Enoxaparin 30 mg twice daily (BID) is a common regimen for chemoprophylaxis. However, differences in enoxaparin metabolism based on body weight may influence its efficacy and safety profile.ObjectiveTo assess the association between BMI and postoperative VTE and hematoma rates in patients treated with prophylactic enoxaparin 30 mg BID.Design, Setting, and ParticipantsThis was a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…In our study, patients with a VTE event had significantly higher mean BMI values than patients who did not develop a postoperative VTE. This is consistent with our previous study, where BMI greater than 30 was identified as an independent risk factor for inadequate prophylaxis and increased VTE events 24 . In addition, in a previous prospective study, we found that BMI is a significant predictor of antifactor Xa levels after controlling for multiple variables 23 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, patients with a VTE event had significantly higher mean BMI values than patients who did not develop a postoperative VTE. This is consistent with our previous study, where BMI greater than 30 was identified as an independent risk factor for inadequate prophylaxis and increased VTE events 24 . In addition, in a previous prospective study, we found that BMI is a significant predictor of antifactor Xa levels after controlling for multiple variables 23 .…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with our previous study, where BMI greater than 30 was identified as an independent risk factor for inadequate prophylaxis and increased VTE events. 24 In addition, in a previous prospective study, we found that BMI is a significant predictor of antifactor Xa levels after controlling for multiple variables. 23 These findings relate to the changing strategy of VTE chemoprophylaxis by implementation of weight-based dosing protocols.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Prior studies have estimated that every acute VTE event costs $12,000–15,0000 to treat, without counting the subsequent complications (Grosse et al, 2016; Veeranki et al, 2021). Patients undergoing microsurgical reconstruction of the head and neck (H&N) region are at increased risk of developing VTE due to the extended surgery time, malignancy itself, and immobilization after the surgery (Bahl et al, 2014; Chen et al, 2008; Eley et al, 2013; Garritano et al, 2013; Garritano & Andrews, 2016; Saadoun et al, 2021; 2022; Venkatesh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In current clinical practice, peri‐ and post‐operative chemoprophylaxis (enoxaparin, heparin [UFH], or aspirin) has become the standard of care after major H&N surgery (C. J. Pannucci et al, 2011; Christopher J. Pannucci et al, 2021; Venkatesh et al, 2020). However, breakthrough VTE can occur even in the presence of chemoprophylaxis (Ong et al, 2017; Christopher J. Pannucci et al, 2021; Tipirneni et al, 2021; Venkatesh et al, 2020; Saadoun et al., 2022). In fact, VTE risk has been reported between 1.4% to 6% when patients received antithrombotic agents perioperatively (Bahl et al, 2014; Chen et al, 2008; Moreano et al, 1998; Ricci et al, 2016; Thai et al, 2013; Venkatesh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%